Testing the role of skepticism in Islamic banks: evidence from Indonesia - Aidha Trisanty; Budhi Haryanto; Catur Sugiarto; Lilik Wahyudi (Cogent Business & Management, 2024)
Although there have been several studies on customer intention, no research has specifically examined how skepticism toward Shariah claims affects customer intention in Islamic banking. This study tests the factors influencing customer intentions based on the theory of planned behavior in the context of Islamic banking. Compliance, religiosity, and Islamic Financial Literacy (IFL) variables were used as antecedents of skepticism. This study employed a quantitative research approach utilizing online questionnaires for data collection. Data were collected through an online survey using convenience sampling (a nonprobability sampling technique). The respondents were Muslims in Indonesia who did not have funding or financing accounts in Islamic banks. The sample comprised 210 valid responses. Data analysis was conducted using partial least-squares structural equation modeling. The findings indicate that consumer skepticism toward Shariah claims in Islamic banks is influenced by compliance, religiosity, and IFL and that skepticism affects customers' intention to use Islamic banks. This study is the first to examine consumer skepticism and its impact on user intentions in the context of Islamic banking. Therefore, this study provides insights into how consumer skepticism toward Shariah claims in Islamic banks is formed, which can serve as input for Islamic banking practitioners to implement appropriate marketing strategies.
Keywords: 650; Islamic banking; intention to use; skepticism; compliance; religiosity; islamic Financial literacy